Memory for the Future: Psychodynamic Approach to Time and Self Through the Default Network - Cieri, Filippo (Frontiers in Human Neuroscience, 2022)
Time exists in us, and our self exists in time. Our self is affected and shaped by time to the point that a better understanding of the former can aid the understanding of the latter. Psychoanalysis works through self and time, where the self is composed of the biopsychosocial history (the past) of the individual and able to map a trajectory for the future. The psychoanalytic relationship starts from a “measurement”: an active process able to alter the system being measured - the self - continuously built over time. In this manuscript, an association between time and self will be proposed, suggesting a neural overlapping at the Default Network. A historical and scientific background will be introduced, proposing a multidisciplinary dimension that has characterized the birth of psychoanalysis (its past), influencing its present and future in the dialogue with physics and neuroscience. After a historical scientific introduction, a neural entanglement between past and future at the Default Network level will be proposed, tracing a link with the self at the level of this network. This hypothesis will be sup-ported by studies in cognitive neurosciences and functional neuroimaging which have used the resting state functional Magnetic Resonance Imaging. The ontogenetic development of time perception will be discussed, consistent with self-development and the Default Network’s function. The most common form of dementia, the Alzheimer Disease, in which the perception of time is brutally impaired together with a loss of the self’s functions will be proposed to support this idea. Finally, the potential theoretical and clinical significance for psychoanalysis and psychodynamic neurosciences, will be discussed.